2013
DOI: 10.1590/0104-1169.2943.2374
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between subjective social status and perceived health among Latin American immigrant women

Abstract: OBJECTIVE: to explore the relationship between socioeconomic status and subjective social status and explain how subjective social status predicts health in immigrant women. METHODS: cross-sectional study based on data from 371 Latin American women (16-65 years old) from a total of 7,056 registered immigrants accesse through community parthers between 2009-2010. Socioeconomic status was measured through education, income and occupation; subjective social status was measured using the MacArthur Scale, and perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 14 publications
4
18
1
Order By: Relevance
“…Subjective social status may also tap into migration and immigrant-related stressors likely to affect perceptions of relative worth and health, such as discrimination and economic hardship [24,[27][28][29][30][31][32]. A few studies show a subjective social status health effect among Latino immigrants adjusting for socioeconomic status [18,20,33]. Research analyzing the same data as this study found Latino immigrants who experience downward social mobility are at elevated risk of poor health [34,35].…”
Section: Salience Of Nativity Statusmentioning
confidence: 69%
See 1 more Smart Citation
“…Subjective social status may also tap into migration and immigrant-related stressors likely to affect perceptions of relative worth and health, such as discrimination and economic hardship [24,[27][28][29][30][31][32]. A few studies show a subjective social status health effect among Latino immigrants adjusting for socioeconomic status [18,20,33]. Research analyzing the same data as this study found Latino immigrants who experience downward social mobility are at elevated risk of poor health [34,35].…”
Section: Salience Of Nativity Statusmentioning
confidence: 69%
“…The subjective status-health relationship appears to vary, in part, by race/ethnicity [11][12][13][14][15][16]. Though studies in Latin America have examined the subjective status-health relationship, few have tested this association among United States Latinos [11,[17][18][19][20][21]. This is an important research gap as U.S. Latinos, a multi-ethnic population, are on average disproportionately burdened by low incomes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the SF-36 has been shown to have adequate internal consistency and construct validity among Hispanics (Katerndahl, Amodei, Larme, & Palmer, 2002; Peek, Ray, Patel, Stoebner-May, & Ottenbacher, 2004), equivalent response patterns on the PHQ-9 have been found between English and Spanish-speaking Hispanic women (Merz, Malcarne, Roesch, Riley, & Sadler, 2011), and both our measures of objective cognitive function (Manly et al, 2011), and subjective cognitive complaints (Alders & Levine-Madori, 2010; Lagana & Sosa, 2004) have been used in previous studies of Hispanics. In contrast, findings on the psychometric properties of our measure of anxiety symptoms in Hispanics have been mixed (Asner-Self, Schreiber, & Marotta, 2006; Prelow, Weaver, Swenson, & Bowman, 2005; Torres, Miller, & Moore, 2013; Wiesner et al, 2010), and there is limited published research on the psychometric properties among Hispanics of the scales used to assess social functioning, positive psychological traits, and religiosity/spirituality (Katerndahl et al, 2002; Sanchon-Macias, Prieto-Salceda, Bover-Bover, & Gastaldo, 2013). …”
Section: Methodsmentioning
confidence: 95%
“…Study populations range from representative samples of the USA and EU states [14][15][16][17], to large samples with civil servants from the UK and Brazil [10,18 & ,19], to children and adolescents [20 & , 21-23], to middle-aged and elderly populations [24][25][26][27][28][29], to ethnically diverse samples [8,30,31], to populations from developing countries [32][33][34][35], to immigrants [36][37][38], to pregnant women [39] and different clinical samples [40][41][42][43][44][45]. Findings from these studies indicate that lower SSS is related to several health indicators and risk factors for disease, including lower self-rated health, depressive symptoms, higher substance use, impaired sleep quality, functional decline, poor healthcare, food insecurity, poor oral health, biological risk factors, respiratory illness, reduced cardiovascular health, diabetes and mortality.…”
Section: Introductionmentioning
confidence: 99%